The Concept of Morality and Values Education in Islamic Education - Hartinawanti H; Syahruddin Usman; Syarifuddin Ondeng (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Islamic education has a strategic role in shaping the morality of individuals and society through the comprehensive internalization of Islamic values. The phenomenon of a moral crisis, characterized by increasing deviant behavior, low integrity, and weakening social values, has become a major challenge for today's educational world. This article aims to examine the concept of morality from the perspective of Islamic education, the nature of value education, strategies for implementing value education, as well as the challenges of value education in the modern era. The method used is a literature review with a descriptive-analytical approach. The study results show that morality in Islam is rooted in the concept of akhlak (character) derived from the Quran and Hadith. Values education in Islam is holistic, integrative, and transcendental, encompassing human relations with Allah, fellow humans, and the environment. The implementation of values education is carried out through role modeling, habituation, integration of values in learning, direct experience, moral reflection, strengthening of school culture, Islam-based digital literacy, as well as spiritual reinforcement. In the modern era, values education faces challenges such as cultural globalization, digital technology disruption, dominance of cognitive approaches, a crisis of role models, and weak synergy between family, school, and society. Therefore, an adaptive values education strategy is needed without losing the essence of Islamic values.